THE STATUS OF MOLLUSK DIVERSITY AND PHYSICAL SETTING OF THE MANGROVE ZONES IN CATANDUANES ISLAND, LUZON, PHILIPPINES - JIMMY TEVAR MASAGCA; ANGELICA V. MENDOZA; ESTERELLA T. TRIBIANA (SEAMEO BIOTROP, 2010)
The status of mollusk diversity and physical setting of mangrove areas in Catanduanes island, Luzon (Philippines) are described. A total of 57 species of molluscs, consisting of 27 gastropods and 30 bivalves were recorded in the island. The most abundant of these molluscs are the prosobranch, Terebralia sulcata; corbiculid bivalve, Geloina coaxans; potamidiids, Cerithidea cingulata and Cerithidea rhizophorarum; and two other species of the genus Littorina (Littorinopsis). Using the physiographic model, majority of the mangrove areas under study follow the composite river and wave-dominated setting with some few areas having the wave-dominated, tide-dominated allochthonous setting following the physiognomic model. Keywords: Mollusk diversity, mangrove areas, Philippines